Experimental Investigation on BN-Based Flexible Composite Phase-Change Material for Battery Module - Tang, Xianwen; Deng, Jian; Wu, Zixin; Li, Xinxi; Wang, Changhong (Frontiers in Energy Research, 2022)
Towards to the application of composite phase change material (CPCM) in electric vehicles, which suffers from leakage, high rigidity, and low thermal conductivity. In this study, a novel flexible composite phase change material (CPCM) with high thermal conductivity and low leakage has been proposed presented and utilized in battery module. Among these, Polyethylene glycol (PEG) as phase change component, styrene-butadiene-styrene (SBS) as support material and ethylene-propylene-diene monomer (EPDM) as assisted packaging material could greatly enhanced the flexibility and deformability of CPCM. Besides, boron nitride (BN) was adopted to enhance the heat dissipating capacity and reduce the temperature difference in the module. In addition, compared with other cooling methods, the battery module with compact and efficient advantages analyzed at different discharge rates. The results revealed that the flexible CPCM controlled below 44.8°C and the temperature difference maintained within 5.6°C at 3 C discharge rate. Even during the charge–discharge cycles, it displayed lower temperature fluctuation within the acceptable range. These outstanding shape recovery and anti-leakage performances of BN based flexible CPCM would provide insights into battery module with desirable assembly method and process flexibility.